The transformation of nature images in contemporary dance - Xinyi Zhang (ХДАК, 2025)
Dance, as an ancient and unique art form, has carried rich emotional expression, cultural inheritance and social function since the beginning of human civilization. In the long historical evolution, the dance continuously develops and evolves, from the ritual dance of primitive tribes, to the elegant dance of the court, to the diversified dance styles of today, it has always been closely intertwined with the development of human society.
qualification work for obtaining master’s degree in specialty 024 Choreography
Keywords: хореографія народна; хореографія класична